2023
DOI: 10.1039/d2na00790h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steric hindrance on the interfacial connection of MOF-on-MOF architectures

Abstract: MOF-on-MOF is attracting great attention due to its improved and/or synergistic properties not exhibited in a single MOF. In particular, the non-isostructural pairs of MOF-on-MOFs can have great potentials induced...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Finally, the stability of proposed MOF-on-MOF pairs is evaluated through DFT calculation that provides the net energy stabilization, which considers both the energy penalty from linker strain and the energy stabilization from the bond formation. Subsequent studies have shown that the energy barrier at the interface plays a crucial role in the stability of the final material . The applicability of this algorithm’s predictions was confirmed with successful synthesis of six MOF-on-MOF pairs using standard solvothermal MOF synthesis methods.…”
Section: Chemiresistors Based On Mof-on-mof Architecturesmentioning
confidence: 66%
See 3 more Smart Citations
“…Finally, the stability of proposed MOF-on-MOF pairs is evaluated through DFT calculation that provides the net energy stabilization, which considers both the energy penalty from linker strain and the energy stabilization from the bond formation. Subsequent studies have shown that the energy barrier at the interface plays a crucial role in the stability of the final material . The applicability of this algorithm’s predictions was confirmed with successful synthesis of six MOF-on-MOF pairs using standard solvothermal MOF synthesis methods.…”
Section: Chemiresistors Based On Mof-on-mof Architecturesmentioning
confidence: 66%
“…Subsequent studies have shown that the energy barrier at the interface plays a crucial role in the stability of the final material. 122 The applicability of this algorithm's predictions was confirmed with successful synthesis of six MOF-on-MOF pairs using standard solvothermal MOF synthesis methods. Conversely, the mismatched pairs result in separately grown crystals or polycrystalline core−shell structures with an excess of the shell MOF.…”
Section: ■ Chemiresistors Based On Mof-on-mof Architecturesmentioning
confidence: 77%
See 2 more Smart Citations
“…[60][61][62][63] Typically, the assembly of MOF-on-MOF configurations is involved in the arrangement of two or more MOF species through lattice matching. [64][65] Researchers commonly select easy-to-prepare and stable MOFs as templates for the secondary growth of MOFs by externally introducing metal ions and organic linkers. [66][67]102] In cases of high lattice compatibility, secondary MOFs can effectively nucleate and grow atop primary MOF substrates.…”
Section: Introductionmentioning
confidence: 99%